2011
DOI: 10.1080/11287462.2011.10800705
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Human Health in Indigenous Communities in Canada

Abstract: Each year in Canada, there are an estimated 90 deaths and approximately 90,000 illnesses caused by contaminated drinking water. These estimates are likely low due to under-reporting. A disproportionate number of these illnesses occur in Indigenous communities where poor water quality, inadequate treatment of drinking water, lack of running water and poor sanitation, and substandard health services all contribute to a growing public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Using the WHO water standard (WHO 2011 ), the current study found that the microbial quality of household-stored drinking water in most of the stored drinking water samples from both households with U5 children with diarrhea and households with U5 children without diarrhea was contaminated with FC. Consistent with our findings, a study in Canada showed that exposure to water-borne pathogens and lack of sanitation contributed to major health issues in some communities (Metcalfe et al 2011 ). Similarly, a study in southern Ethiopia identified FC in 80% of drinking water samples, with counts ranging between 0.67 and 266.67 CFU/100 ml (Yasin et al 2015 ).…”
Section: Resultssupporting
confidence: 92%
“…Using the WHO water standard (WHO 2011 ), the current study found that the microbial quality of household-stored drinking water in most of the stored drinking water samples from both households with U5 children with diarrhea and households with U5 children without diarrhea was contaminated with FC. Consistent with our findings, a study in Canada showed that exposure to water-borne pathogens and lack of sanitation contributed to major health issues in some communities (Metcalfe et al 2011 ). Similarly, a study in southern Ethiopia identified FC in 80% of drinking water samples, with counts ranging between 0.67 and 266.67 CFU/100 ml (Yasin et al 2015 ).…”
Section: Resultssupporting
confidence: 92%
“…Indeed, substandard, unreliable water services have contributed to issues with insufficient water 77 quantity, water contamination, and frequent and / or long-standing boil water advisories in many 78 Indigenous communities (Daley et al, 2014;Patrick, 2011). In Canada, a growing body of 79 literature exists describing these persistent drinking water issues in First Nations communities 80 (Basdeo and Bharadwaj, 2013;Dupont et al, 2014, 2010, Eggertson, 2008Harden and 81 Levalliant, 2008;Metcalfe et al, 2011); however, less is published regarding Inuit communities in northern Canada. Water-related issues in Inuit communities are often due to their unique and 83 challenging geography, climate, financial and human resources, and infrastructure (Marino et al, 2009;Medeiros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous communities in Canada experience more drinking water security challenges than non‐Indigenous communities (Metcalfe et al., 2014; Health Council of Canada, 2005). Canada holds seven percent of the world's fresh water, yet it is inhabited by less than 0.5 percent of the world's population (Environment Canada, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%